Rhabdomyosarcoma of the Oral Cavity: A Case Report - Miloglu, Ozkan; Altas, Sare Sipal; Buyukkurt, Mustafa Cemil; Erdemci, Burak; Altun, Oguzhan (European Journal of Dentistry, 2011)
Rhabdomyosarcoma (RMS), a tumor of skeletal muscle origin, is the most common soft tissue sarcoma encountered in childhood and adolescence. The common sites of occurrence are the head and neck region, genitourinary tract, retroperitonium, and, to a lesser extent, the extremities. In the head and neck region, the most commonly affected sites are the orbit, paranasal sinuses, soft tissues of the cheek, and the neck. RMS is relatively uncommon in the oral cavity, and the involvement of the jaws is extremely rare. Here, we report a case of oral RMS in a 13-year-old child and describe the clinical, radiological, histopathological, and immunohistochemical findings. (Eur J Dent 2011;5:340-343)
Keywords: Mouth neoplasm; Oral pathology; Alveolar rhabdomyosarcoma; Radiotherapy; Chemotherapy